18x-3(x+19)=40x-7

Simple and best practice solution for 18x-3(x+19)=40x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-3(x+19)=40x-7 equation:



18x-3(x+19)=40x-7
We move all terms to the left:
18x-3(x+19)-(40x-7)=0
We multiply parentheses
18x-3x-(40x-7)-57=0
We get rid of parentheses
18x-3x-40x+7-57=0
We add all the numbers together, and all the variables
-25x-50=0
We move all terms containing x to the left, all other terms to the right
-25x=50
x=50/-25
x=-2

See similar equations:

| 2n3+24n2-56=0 | | 9+(2x−2)=3 | | 10x−6=5x+4 | | 10−x=1 | | +9x=-20 | | 225=49-v | | 15=3y-15 | | m28m1=0 | | 2(x-3)/3x+1=3/10 | | (x=2)^2=20 | | x/3+8x/4-3/6=x+7/2 | | 3x-x=4+2 | | 5p-10=-30 | | 3((n-5)=21 | | 5t+30=10 | | 5x-13=8x-14 | | -10p÷9p=12 | | 9w=33=12w-27 | | 1/5x10=5 | | n-10=(15-n)/3 | | m+17=40 | | 4z-2z(1-4)=36 | | 2(3-2)-5=3-(2+x) | | 8x+7x+6x+5x=100 | | 1/5h+9=15 | | 1/5h-9=15 | | |5-4x|=|2x+13| | | 3m=5m-12 | | x²+5x+400=0 | | g-8=21 | | 5x+4–2x+10=2x–23+13+7x | | g-5=29 |

Equations solver categories